University hospital status and prognosis following surgery for esophageal cancer. Issue 8 (August 2016) - Markar, S.R.; Wahlin, K.; Lagergren, P.; Lagergren, J.
Abstract: Background: We hypothesized that such prognosis is independently improved by surgery conducted within university hospitals. Methods: Patients undergoing esophagectomy for esophageal cancer between 1987 and 2010 with follow-up until 2014 were identified from population-based nationwide Swedish cohort study. The association between university hospital status in and mortality was analyzed using a multivariable Cox-proportional hazards model, providing hazard ratios (HRs) with 95% confidence intervals (CIs). The HRs were adjusted for surgeon volume as well as age, comorbidity, tumor stage, histological subtype, neoadjuvant therapy and calendar period. Results: Among 1820 included patients, 989 (54.3%) had surgery at one of the six university hospitals. Of the 83 and 569 patients operated on by the higher surgeon volume (17–46 cases) and middle surgeon volume groups (7–16 cases), 60 (72.3%) and 430 cases (75.6%) respectively were performed within university hospitals. University hospitals status indicated a non-significant reduction in all-cause 90-day mortality (HR = 0.82, 95% CI 0.61–1.10), but all-cause 5-year (HR = 0.94, 95% CI 0.83–1.05) and disease-specific 5-year mortality (HR = 1.00, 95% CI 0.88–1.14) were similar to non-university hospitals. Higher surgeon volume (17–46 cases), showed non-significant reductions in all-cause 90-day (HR = 0.49, 95% CI 0.21–1.14), all-cause 5-year (HR = 0.80, 95% CI 0.61–1.06) and disease-specific 5-year mortality (HR = 0.81, 95% CI 0.60–1.09). Conclusions: This study found no improvements in long-term mortality from esophagectomy performed within university hospitals after adjustment for surgeon volume and other confounders.